A autoavaliação institucional participativa na educação infantil do município de São Paulo - Martins, Márcia Gomes (2016)
The objective of this research was to accompany and to analyze the participation of the educational community's different segments, in the self-institutional assessment participatory in two units of early childhood education in the city of São Paulo, that assists children aged 4-5 years. The self-assessment was accomplished tends for base the Quality Indicators in Early Childhood Education in the city of São Paulo, document elaborated by the City Department of Education of São Paulo with the purpose of subsidizing the education units of childhood education, of the direct and indirect net, in the self-assessment process. The analysis of the interviews accomplished in the two units reveals that the educational community's representatives believe that they were represented in the self-assessment and they wait that the proposals listed in the action plan, as much the one of competence of the unit as the one of competence of the City Department of Education of São Paulo, be rendered and provide improvements for the social quality of the early childhood education. This process evaluative, if well accompanied by the official organs, it can become an important step for the establishment of an evaluative culture with views to the improvement of the social quality of the childhood education in the city of São Paulo